Context-Responsive Managerial Skills and Character-Centred School Quality: Implications for SDGs 4, 16, and 17 in Eastern Indonesia - Remigius Missa; Maria Veronika Roesminingsih; Bambang Sigit Widodo (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To examines how principals integrate conceptual, human, and technical managerial skills to strengthen school quality across three Catholic secondary schools in Eastern Indonesia and interprets the relevance of these practices to SDGs 4, 16, and 17. Method: A multi-site case study was conducted in three schools governed by the same foundation but differentiated by mission, resources, and performance conditions. Purposively selected participants represented principals, vice-principals, teachers, and foundation leadership; the source documentation did not provide one consolidated participant total. Data from in-depth interviews, participant observation, and documentary analysis were examined within each site through condensation, display, and conclusion drawing, followed by cross-site comparison and triangulation. Results: Conceptual skill was expressed through school self-evaluation, SWOT analysis, vision and mission review, priority setting, and the alignment of school work plans and budgets. Human skill mobilised implementation through motivation, dialogue, active listening, recognition, delegation, stakeholder participation, and partnership building. Technical skill embedded priorities in instructional supervision, curriculum and assessment coordination, teacher development, remedial and enrichment support, learning-resource management, discipline, and accountable administration. Across the sites, these skills operated as a recursive improvement process. School quality combined standards compliance and academic and non-academic performance with integrity, character, faith, civic responsibility, local wisdom, and social trust. Novelty: The study advances Katz’s framework from a three-part taxonomy to a context-responsive improvement mechanism and offers a character-centred conception of school quality for faith-based and resource-differentiated settings, while linking the findings analytically-not as original field indicators—to the governance principles of SDGs 4, 16, and 17.